Co-activation of TGF-ß and cytokine signaling pathways are required for neurotrophic functions - Unsicker, Klaus; Krieglstein, Kerstin (Cytokine & growth factor reviews, 2000)
This article summarizes and interprets recent data from our laboratories suggesting that transforming growth factor-ß (TGF-ß1, -ß2, -ß3) is essentially required, in vitro and in vivo, for the neurotrophic signaling of glial cell line-derived neurotrophic factor (GDNF). TGF-ß, which is synthesized by and released from neurons, also synergizes with neurotrophins and members of the neurokine and fibroblast growth factor families by increasing their efficacies. However, when applied to purified neuron populations without other factors being added, TGF-ß does not promote survival or differentiation. Together, these data suggest that neither TGF-ß nor GDNF fulfil essential criteria of a typical neurotrophic factor, as e.g. nerve growth factor (NGF). Moreover, the neurotrophic activity of NGF and other classic neurotrophic factors is apparently based, to a significant extent, on their co-operativity with TGF-ß. Mechanisms, by which TGF-ß generates neurotrophic effects and synergizes with other cytokines are beginning to emerge. Recruitment and/or stabilization of receptors and cross-talks at different levels of signal transduction are likely to be implied in generating the neurotrophic potential of the TGF-ß/cytokine synergisms. Together, these data outline a novel role of TGF-ß in a key event of nervous system development, ontogenetic neuron death. Conceptually more important, however, may be the broadening of the neurotrophic factor concept, which now has to imply the possibility that two cytokines, each being ineffective by itself, become neurotrophically active when acting in concert.